Pengaruh Metode Pembelajaran Problem Based Learning terhadap Peningkatan Hasil Belajar PAI Di SMPN 2 Ulaweng Kabupaten Bone - Primadoniati, Anna (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This article examines the influence of problem based learning method to increase PAI learning outcomes in SMP 2 Ulaweng. By using quantitative analysis, the results of research are obtained; The impact of the LBL can be seen based on the results of student observations and the results of the experiment group posttest higher than the control group. In addition, based on motivational indicators learn PIE group of experiments showed better results i.e. most students have been actively asked, dare to respond to friends and teacher statements, can work equally well in groups , andconfidently presenting the results of the discussion in front of the class. In addition, with this PBL group of experiments showed the solidarity between the group members by using the LBL then students will gain several benefits, among others: increased problem solving skills, building Leadership and cooperation, learning skills,and motivating students to learn. In the Learning control class, the lecture and Q amp; A method does not give students an opportunity to optimize their skills. Based on the observation guidelines the results of students who are active during learning are high-achievement students in the classroom. While students who are not accustomed to actively ask and respond to other friends' statements.